Women of Color in the Health Professions: A Scoping Review of the Literature - Olihe Okoro; Omolayo Umaru; Meghana Ray (MDPI AG, 2024)
Women of color (WoC) in the health professions encounter challenges in advancement to higher positions, disparities in wages, discrimination, lack of expectation to achieve leadership positions, and absence of extensive support networks. Articles in the literature have addressed race and/or gender in the context of professional development. However, applying an intersectional lens or framework to better understand the contextual issues of professional development for WoC remains to be addressed. Thus, this scoping review aimed to (i) identify health professions literature that addresses disparities affecting WoC, and (ii) describe strategies and approaches to support WoC in the health professions. Methods: The literature searches were conducted in multiple databases, including PubMed and MEDLINE (Ovid); and Google and Google Scholar were used to "hand search" further articles including gray literature. Three independent reviewers reviewed and screened articles for inclusion in accordance with a guide. Search included articles on pharmacy or healthcare professions, published in English, and which met three content criteria: racial disparities/inequities, professional development/career advancement, and women or gender disparities Results: A total of 31 articles were included-medicine (17), nursing (1), pharmacy (7), other (4), and multiple health professions (2). Key findings included underrepresentation of women and minority groups, inequities in professional advancement and leadership positions for WoC, and greater dissatisfaction and attrition among minority and women professionals. Conclusion: WoC face unique and distinct challenges and barriers in their professional careers resulting from the intersectionality of not only race and gender, but also lived experiences and opportunities. Strategies to improve diversity and representation should include an intersectional framework or lens and be critically evaluated.